CRIMINOLOGICAL STUDY OF TAX CORRUPTION PERSONS - Rahman Pakpahan, Vicky Aulia; Simatupang, Nursariani (Inspiring Law Journal, 2024)
The problem of corruption in Indonesia is quite worrying, especially the tax evasion that occurred at the Aceh Singkil bank by using their position to carry out their acts of corruption. Formulation of the problem: what is the mode of tax corruption, the factors that cause corruption, overcoming perpetrators of tax corruption. The research method used is a normative juridical research type with primary, secondary and tertiary legal materials with descriptive analytical research characteristics. This research uses data collection techniques using library research. Based on the results of the research, the modus operandi in the corruption case at Bank Aceh Singkil was that an employee named Joly Rusli committed a criminal act of tax corruption during the 2017-2020 period by borrowing his friend's ID card, making it appear as if he was making a deposit to the bank but actually diverting the money to an account. personal. As a result, the state suffered a loss of 1.4 billion rupiah. Joly Rusli was charged with Article 2 and Article 3 concerning criminal acts of corruption. The causal factor in this case, an employee of Bank Aceh Syariah Aceh Singkil Branch, is suspected of corrupting regional tax funds amounting to IDR 1.4 billion for personal gain, showing a big drive to increase personal wealth as the main motive. This greedy and greedy nature is one of the triggering factors for corruption that originates from within and weak morals and weak internal supervision of Aceh sharia banks can lead to corruption carried out by Jolly Rusly. Efforts to overcome tax corruption include refunding funds: perpetrators who are proven guilty are usually required to return the funds they have corrupted or avoided paying. and weak internal supervision and tightening supervision on banks so that the same incident will not happen again. And the perpetrator has been dismissed by the competent authority in this case, namely the Aceh Singkil regional tax office